Pengaruh Budaya Organisasi terhadap Kinerja Pegawai - Ramadhany, Ridha; Intan Kumalasari; Murraya Putri Palupi (Public Service and Governance Journal, 2025)
Organizational success will be achieved if a positive work culture motivates individuals to work with high intensity. The purpose of this study is to measure how much influence organizational culture has on the performance of employees of the South Sulawesi Provincial Health Office. The research method used is a case study where variables are measured on a Likert scale of 1-5. The population taken was 263 employees then selected based on a 10% significant level sampling to 73 people. Data collection used survey, observation and documentation methods, while data analysis used a multiple regression model through SPSS version 29. The results of the study obtained 1) The simultaneous influence of organizational culture on performance has an impact of 47.78% (moderate). 2) The partial influence of the dimensions of Involvement, Consistency and Adaptability does not show a significant influence on Performance. However, the Mission dimension is proven to have a significant impact so that employees tend to focus more on working effectively and efficiently. 3) Descriptive analysis of Denison's organizational culture model at the South Sulawesi Provincial Health Office emphasizes Involvement which tends towards team orientation on cooperation, collaboration and involvement of team members so as to create employee satisfaction to prevent conflict in the organization. A good organizational culture will create a balanced atmosphere, which is reflected in work productivity, motivation, and employee commitment.